Knowledge management model for micro and small computer companies - Francisco-Paredes, Adam A. (2019)
The objective of the research is to present a model of knowledge management for micro and small enterprises engaged in the sale of computers and software; for which we have considered the identification of activities that generate knowledge, the mechanisms that contribute to communication, communication control and integration of knowledge; as well as the identification and understanding of the contextual elements associated with communication, control and generation of knowledge. These elements were analyzed through the study of five cases in qualitative research and thirty respondents in quantitative research. The interview, direct observation, documents and surveys were the main data collection methods used in the study and the empirical validation of the model of knowledge management. The results indicate that the generation of knowledge depends on the technical personnel of enterprises; regarding the dissemination and exchange of knowledge, this depends on a climate and organizational culture open and receptive to the actors of communication: the transmitter and receiver, where the effective participation of the issuer causes the receiver feeds back to relying on communication consolidating acquired prior knowledge or against resistance or obstacle to success. The communication control depends on the elements that help and hinder them can be monitored under indicators to strengthen through feedback. On the other hand the integration of knowledge depends on a climate and organizational culture that encourages assimilation of knowledge in employees where the exchange of technical staff, for the development of projects, and the recruitment of qualified personnel are not obstacles to the four processes.